2017
DOI: 10.1002/pola.28509
|View full text |Cite
|
Sign up to set email alerts
|

Reversible addition-fragmentation chain transfer polymerization of alkyl-2-cyanoacrylates: An assessment of livingness

Abstract: Alkyl 2‐cyanoacrylates (CAs) are primarily used as instant adhesives, including those sold under the Loctite brand. The adhesive action can be inhibited with acid stabilizers allowing radical polymerization to be employed. The following article details the first attempted controlled/living radical polymerization of alkyl CAs: Reversible addition fragmentation chain transfer (RAFT) polymerization mediated by a poly(methyl methacrylate) dithiobenzoate macroRAFT agent for three different CA monomers (ethyl 2‐cyan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…These act by proton transfer to terminate anionic or zwitterionic species, before significant chain growth occurs. Anionic inhibitors have included Lewis acids, such as BF 3 complexes [48], as well as, acetic acid [50,51,52,53], dichloroacetic acid [54], trifluoroacetic acid [55], methanesulfonic acid [47], and 1,3-propanesultone [51,56,57,58]. Excessive acidity should, however, be avoided, due to the potential for the hydrolysis of the monomer/polymer ester functionality leading to interference with the polymerization (see above).…”
Section: Conventional (Non-living) Radical Polymerizationsmentioning
confidence: 99%
See 3 more Smart Citations
“…These act by proton transfer to terminate anionic or zwitterionic species, before significant chain growth occurs. Anionic inhibitors have included Lewis acids, such as BF 3 complexes [48], as well as, acetic acid [50,51,52,53], dichloroacetic acid [54], trifluoroacetic acid [55], methanesulfonic acid [47], and 1,3-propanesultone [51,56,57,58]. Excessive acidity should, however, be avoided, due to the potential for the hydrolysis of the monomer/polymer ester functionality leading to interference with the polymerization (see above).…”
Section: Conventional (Non-living) Radical Polymerizationsmentioning
confidence: 99%
“…In order to study the radical polymerization of CAs, inhibitors should be removed by distillation prior to commencing the reaction [58]. Any glassware that will come in contact with CAs should be acid washed, acetone rinsed, and oven dried before use.…”
Section: Conventional (Non-living) Radical Polymerizationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Random cyanoacrylate copolymerization with vinyl monomers has been reported by radical,24,25 and metal catalysed initiators 26. Recent studies showed that the use of RAFT agents did not promote ideal living block polymerization of CA 27…”
mentioning
confidence: 99%